Premium ethylcellulose polymer based architectures at work in drug delivery - Oluwatoyin A. Adeleke (Elsevier, 2019)
Premium ethylcellulose polymers are hydrophobic cellulose ether based biomaterials widely employed as biocompatible templates for the design of novel drug delivery systems. They are classified as United States Food and Drug Administration Generally-Recognized-As-Safe chemical substances and have been extensively utilized within the biomedical and pharmaceutical industries for over half a century. They have so far demonstrated the potential to modulate and improve the physiological performance of bioactives leading to the desired enhanced prophylactic and therapeutic outcomes. This review therefore presents a scholarly survey of inter-disciplinary developments focused on the functionalities of ethylcellulose polymers as biomaterials useful for the design of smart delivery architectures for relevant pharmacotherapeutic biomedical applications. Emphasis was placed on evaluating scientific resources related to recent advancements and future directions associated with its applications as delivery systems for drugs and biologics within the past decade thus complementing other specialized reviews showcasing the theme. Keywords: Hydrophobic biomaterial, Cellulose derivative, Polymeric drug delivery, Pharmaceutical excipient, Polymeric biomaterial